John Bristow’s Narcissistic Personality Disorder in Robert Galbraith’s The Cuckoo’s Calling - MUHAMMAD FANANI SEPTIVIAN (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2016)
Abstract John Bristow’s Narcissistic Personality Disorder is the main focus of this study in Robert Galbraith’s The Cuckoo’s Calling. This study applies descriptive analysis method. The main data is taken from the novel written by Robert Galbraith entitled The Cuckoo’s Calling. This thesis is purposed to analyze what causes of John Bristow’s Narcissistic Personality Disorder and the depiction of John Bristow’s Narcissistic Personality Disorder that is already stated in the statement of the problems. The Narcissistic Personality Disorder can occur to individual if their Narcissism healthy development is disturbed by parents that cannot give their proper affection to their children. Theory of narcissism applies from Freud and Kohut for the cause how narcissism become a personality disorder. The theories and concept are well applied to reveal the statement of the problem. The analysis points out that how John Bristow’s early childhood narcissism development stage become unstable due to his mother that doesn’t give him the affection like she gaves to John’s two adoptive siblings and pictured the images of John Bristow’s Narcissistic Personality Disorder in the novel. John kills all his two adoptive siblings so he get to receive the affection from his mother. John acts and behaves with Narcissistic characteristic to get his desired goal. Overall the analysis will verifies and convinces the theory of Kohut on how parents role is important to prevent their children become an adult with Narcissistic Personality Disorder, and also shows the example results when the parents are failed to do so from John Bristow’s actions and behaviours. Keywords : Narcissism, Narcissistic Personality Disorder.